2001
DOI: 10.1074/jbc.m007603200
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Components of the Human Exosome

Abstract: The yeast exosome is a complex of 3 3 5 exoribonucleases. Sequence analysis identified putative human homologues for exosome components, although several were found only as expressed sequence tags. Here we report the cloning of full-length cDNAs, which encode putative human homologues of the Rrp40p, Rrp41p, and Rrp46p components of the exosome. Recombinant proteins were expressed and used to raise rabbit antisera. In Western blotting experiments, these decorated HeLa cell proteins of the predicted sizes. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 39 publications
(68 reference statements)
2
78
0
Order By: Relevance
“…STXBP2 is an interactor of SYNTAXIN 3, which acts on the membrane function and processes of the cell (23); however, it is unclear how knockdown of STXBP2 (directly or indirectly) affects the amount of reverse transcribed HIV-1 proviral DNA. EXOSC5 has been reported to be involved in RNA processing (24). Intriguingly, detailed proteomic data show that this protein interacts with nucleoporin (NUP210), a component of the nuclear pore complex (25), and a novel protein KIAA1217, which engages the TSG101-ESCRT and trans-Golgi pathways (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…STXBP2 is an interactor of SYNTAXIN 3, which acts on the membrane function and processes of the cell (23); however, it is unclear how knockdown of STXBP2 (directly or indirectly) affects the amount of reverse transcribed HIV-1 proviral DNA. EXOSC5 has been reported to be involved in RNA processing (24). Intriguingly, detailed proteomic data show that this protein interacts with nucleoporin (NUP210), a component of the nuclear pore complex (25), and a novel protein KIAA1217, which engages the TSG101-ESCRT and trans-Golgi pathways (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This complex, afterwards referred to as the human exosome, was reported to contain 11-16 subunits ranging from 20 to 110 kDa (Reimer et al, 1986;Gelpi et al, 1990). Size-exclusion chromatography of the human exosome complex in a HeLa cell extract indicated that the cytoplasmic complex has a molecular mass of about 700 kDa (Brouwer et al, 2001); the size previously estimated by glycerol density gradient centrifugation was 300-400 kDa (Mitchell et al, 1997).…”
Section: Yeast Exosomementioning
confidence: 99%
“…RNA helicase KIAA0052 has been reported to associate with the exosome but its role in exosome-mediated RNA degradation is not fully elucidated yet. 13,14 In ARE mediated mRNA decay, RNA helicase RHAU is temporarily recruited to the exosome to facilitate degradation of ARE-containing mRNAs. 14 Recently, the RNA helicase p72 was identified as a factor required for optimal function of ZAP.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%